2021
DOI: 10.1523/jneurosci.0494-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Unbalanced Regulation of α7 nAChRs by Ly6h and NACHO Contributes to Neurotoxicity in Alzheimer's Disease

Abstract: α7 nicotinic acetylcholine receptors (nAChRs) are widely expressed in the brain where they promote fast cholinergic synaptic transmission and serve important neuromodulatory functions. However, their high permeability to Ca2+also predisposes them to contribute to disease states. Here, using transfected HEK-tsa cells and primary cultured hippocampal neurons from male and female rats, we demonstrate that two proteins called Ly6h and NACHO compete for access to α7 subunits, operating together but in opposition to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Homomeric α7 nAChRs are the nicotinic receptors with the highest calcium permeability [ 168 , 169 , 170 ], and too much calcium influx leads to cell injury or death [ 171 ]. Recently, Wu et al [ 172 ] showed that Ly6h antagonizes the effects of NACHO on α7 nAChR assembly in both neurons and HEKtsa cells. Ly6h is a member of the prototoxin Ly6/uPAR protein family [ 173 ] that all have three-finger folding structures similar to snake a-neurotoxins such as a-bungarotoxin [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Homomeric α7 nAChRs are the nicotinic receptors with the highest calcium permeability [ 168 , 169 , 170 ], and too much calcium influx leads to cell injury or death [ 171 ]. Recently, Wu et al [ 172 ] showed that Ly6h antagonizes the effects of NACHO on α7 nAChR assembly in both neurons and HEKtsa cells. Ly6h is a member of the prototoxin Ly6/uPAR protein family [ 173 ] that all have three-finger folding structures similar to snake a-neurotoxins such as a-bungarotoxin [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the CNS, α7 nAChR is located on the surface of various nerve cells including astrocytes, microglia cells, interneurons, and immature granule cells, which are distributed in the basal ganglia, the hippocampus, and the brain gray matter (140)(141)(142). It is believed that α7 nAChR can be involved in many psychiatric and neurological disorders including neuroinflammation, Parkinson's disease, and Alzheimer's disease by regulating neurotransmitter release, synaptic plasticity, and signal transduction (143)(144)(145). The functions of α7nAChR in the nervous system are determined by location, time, and context.…”
Section: Cholinergic Anti-inflammatory Pathwaymentioning
confidence: 99%
“…With the development of the genome-wide association study, a series of studies confirmed that the CHRNA7 genes encoded for the α7 nAChRs in the human brain and the variations within CHRNA7 were associated with the abnormal response of CAP ( 140 , 152 ). In addition, chaperone proteins such as resistance to inhibitors of cholinesterase-3 (RIC3) Ly6h and NACHO could greatly affect the expression and function of nAChRs ( 143 , 153 , 154 ).…”
Section: Neuroimmune Regulation In Saementioning
confidence: 99%
“…The endogenous proteins from the Ly6/uPAR family (Lynx1, Lynx2, Lypd6, Lypd6b, Ly6e, Ly6h, Ly6g6e, PSCA, SLURP-1, SLURP-2) modulate nAChR's function [15][16][17][18][19][20][21][22][23][24][25]. Expression of Lynx1, an α7-nAChR positive modulator in the brain [17,26], is down-regulated in the frontal cortex of 3xTg-AD mice with β-amyloid and tau pathology [27].…”
Section: Introductionmentioning
confidence: 99%